Respiratory acclimatization and psychomotor performance after rapid ascent and during 3 weeks at 3,100 m–A prospective cohort study in healthy individuals - Muralt, Lara; Lichtblau, Mona; Aeschbacher, Sayaka S.; Bisang, Maya; von Gruenigen, Kay; Sooronbaev, Talant M.; Ulrich, Silvia; Bloch, Konrad E.; Furian, Michael (Frontiers in Physiology, 2025)
BackgroundAcclimatization to high altitudes over several weeks has not been extensively studied. Repeated physiological assessments were performed in healthy lowlanders staying at 3,100 m for 3 weeks. We hypothesized that acute exposure to 3,100 m results in hypoxemia, sleep-disordered breathing, and postural instability, while a 3-week acclimatization at 3,100 m will improve these outcomes.MethodsSixteen healthy volunteers (23–33 years) underwent nocturnal pulse oximetry and nasal airflow monitoring during 1 night in Bishkek (760 m), and during nights 1, 8 and 22 at Too-Ashu (3,100 m), Kyrgyzstan. On each day after monitoring, reaction time [psychomotor vigilance test reaction time test, (PVT)] and postural control [center of gravity path length on balance board (COPL)] were assessed.ResultsCompared to 760 m, mean nocturnal SpO2 dropped in the first night at 3,100 m from mean ± SD 94.8% ± 1.9% to 86.3% ± 2.9% and recovered partially to 89.8% ± 1.5% after 3 weeks (P < 0.05 both comparisons to 760 m). Corresponding median (quartiles) oxygen desaturation indices were 1.0/h (0.3; 2.2), 6.5/h (4.5; 12.1) and 6.4/h (4.2; 11.1) time in bed (P < 0.05 both comparisons to 760 m). Median (quartiles) reaction times were 226 ms (212; 231), 236 ms (210; 259) and 228 ms (212; 246), P = NS, all comparisons. COPL worsened from 25.1 ± 4.1cm to 27.1 ± 4.1 cm (P < 0.05) and 26.4 ± 3.7 cm (P = NS compared to 760 m).ConclusionIn healthy lowlanders staying at 3,100 m, nocturnal SpO2 increased over 3 weeks after an initial drop but did not reach baseline values. Postural control was impaired in the first week of acute exposure to high altitude despite improvements in hypoxemia. Altitude exposure did not affect reaction time. Thus, acute and prolonged exposure to hypobaric hypoxia has differential effects on oxygenation, control of breathing, postural control, and reaction time.